Factors Associated with Sarcopenia in Maintenance Hemodialysis Patients: A Cross-Sectional Study - Ria Jauwerissa; Maruhum Bonar H. Marbun; Pringgodigdo Nugroho; Ikhwan Rinaldi; Suhardjono Suhardjono; Hamzah Shatri; Purwita Wijaya Laksmi; Irsan Hasan (Acta Medica Indonesiana)
Background: Sarcopenia is associated with worse outcomes in maintenance hemodialysis (MHD) patients. Differences in criteria and methods used to diagnose sarcopenia, results in a wide range of prevalence. Factors associated with sarcopenia in MHD have not been well-studied. This study aimed to investigate the prevalence and factors associated with sarcopenia in the MHD population. Methods: Observational cross-sectional study was done with 96 MHD patients aged ≥18 years old, with dialysis vintage ≥120 days at Cipto Mangunkusumo Hospital March-May 2022. Descriptive, bivariate, and logistic regression analysis were done to find sarcopenia’s prevalence and association with Simplify Creatinine Index (SCI), type 2 diabetes (DM), Interleukin-6 (IL-6), nutritional status, physical activity, and phosphate serum level. Asian Working Group for Sarcopenia (AWGS) 2019 criteria used to diagnose sarcopenia, Hand Grip Strength (HGS) to identify muscle strength, Bioimpedance Spectroscopy (BIS) to calculate muscle mass, and 6-meter walk test to evaluate physical performance. Results: The prevalence of sarcopenia was 54.2%. Factors with a significant association in bivariate analysis were phosphate serum level (p=0.008), SCI (p=0.005) and low physical activity (International Physical Activity Questionnaire) (p-0.006). Logistic regression analysis found higher phosphate serum level and high physical activity protective of sarcopenia (OR 0.677;CI95% 0.493-0.93 and OR 0.313;CI95% 0.130-0.755 respectively). Conclusion: The prevalence of sarcopenia in the MHD population was 54.2%. Phosphate serum level, SCI, and physical activity were significantly correlated with sarcopenia. Both high phosphate level and high physical activity were protective against sarcopenia.